2021
DOI: 10.1177/10783903211023564
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Perceptions Toward Recovery in Mental Health: A Descriptive Qualitative Study

Abstract: BACKGROUND Recovery in mental health remains inconclusive where the two most prevailing definitions “clinical” and “personal” remain. In nursing schools, students are predominantly taught straightforward concepts of clinical recovery, which result in only a perfunctory and rudimentary understanding of recovery among the undergraduates. AIMS To explore the perceptions of nursing undergraduates on recovery for people experiencing mental health conditions. METHOD A descriptive qualitative study was conducted on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Additionally, because the participating OT undergraduates were taught the biopsychosocial model of MHCs, their characterisation of the causes conformed to that of nursing and medical student populations in Singapore (Chua et al, 2021; Kuek et al, 2022). While this frequently adopted model is rigorous as a basic explanatory tool, the incorporation of cultural factors such as spirituality and religious beliefs may better expose OT undergraduates to the broader lens commonly used in society to perceive MHCs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because the participating OT undergraduates were taught the biopsychosocial model of MHCs, their characterisation of the causes conformed to that of nursing and medical student populations in Singapore (Chua et al, 2021; Kuek et al, 2022). While this frequently adopted model is rigorous as a basic explanatory tool, the incorporation of cultural factors such as spirituality and religious beliefs may better expose OT undergraduates to the broader lens commonly used in society to perceive MHCs.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies on how the medical undergraduates’ attitudes change throughout their training will also provide critical insights into whether our findings will remain similar in the long term. Notable parallels can be drawn from a recent similar study on nursing students from the same medical school in Singapore [ 40 ]. In defining mental illnesses, the participants from both studies demonstrated a similar tendency to rely on biological symptoms and markers pertaining to the brain and established diagnostic criteria such as the DSM.…”
Section: Discussionmentioning
confidence: 99%
“…In defining recovery in mental health, the participants from both studies commonly used the function-defined perspective, referring to the pre-morbid state as a yardstick for functionality. As with the medical undergraduates in this study, the nursing students expressed the sentiment that a return to the pre-morbid state would be unrealistic [ 40 ]. They also held that healthcare professionals should work with patients to determine recovery progress in aspects such as daily living while managing residual symptoms [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations